Quality of life of women with pre-and post-operative breast cancer - Dell’Antônio Pereira, Larissa; Brandão-Souza, Camila; Amaral Musso, Maria Aparecida; Vieira Calmon, Marcela; Costa Neto, Sebastião Benício; Monteiro de Barros Miotto, Maria Helena; Zandonade, Eliana; Costa Amorim, Maria Helena (Investigación y Educación en Enfermería, 2017)
Objective. The objective of this study was to evaluate the Quality of Life (QOL) at the pre and postoperative time of women with breast cancer submitted to surgery and to associate it with the socioeconomic class. Methods. This is a longitudinal study, performed at Santa Rita de Cássia Hospital (HSRC), Vitória - ES, Brazil. The EORTC QLQ instrument C-30 and the EORTC BR-23 were used to measure the QOL of the interviewees before and after breast surgery. Results. A population composed of 87 women, 42.5% were 60 years old or more. The socioeconomic condition C was identified as predominant among the interviewees, covering 62% of the sample (n=54). Women´s QOL in the preoperative period was better in the Physical Function dimensions for class C and D; and the Emotional was better for class B. There was improvement in QOL after surgery for Body Image in class C, and for Social Function in B. Evaluating all social classes, only the dimensions Cognitive Function and Future Perspectives improved in the postoperative period. Conclusion. The quality of life of women after breast surgery worsened in most of the studied dimensions, evidencing the need for an interdisciplinary work dedicated to the recovery and rehabilitation of these patients. How to cite this article: Pereira LDA, Brandão-Souza C, Musso MAA, Calmon MV, Neto SBC, Miotto MHMB, et al. Quality of life of women with pre-and post-operative breast cancer. Invest. Educ. Enferm. 2016; 35(1):